Modelamento e controle de VANTs multirotores em formação - Silva, Renan Cavenaghi (2023)
The Unmanned Aerial Vehicles (UAV) have been extensively researched due to their under- lying characteristics that suit them for different applications such as border surveillance, object recognition, crop spraying and aerial transportation. Despite the enthusiasm from the general community, practical tasks are restricted since the specialized equipment that the UAV have to transport in a mission have limited weight. In this sense, a possible alternative consists of using multiple UAVs in a formation flight to collaboratively transport a heavy-payload. Then, in this dissertation, the dynamic model from an UAV formation is obtained using an approach to parameterize the equation of motion in terms of the number of vehicles, such that different formation configurations can be considered. Moreover, the presented controller involves a leader-follower strategy with virtual-constraints for the vehicles to keep each particular formation. The results show that the employed control strategy is feasible for transporting a heavy-payload despite showing a persistent error due to the unmodeled dynamic from the suspended payload in the formation controller.